Open Source Messaging Application Development: Building and Extending Gaim - Egan, Sean (Apress, 2012)
Gaim is a modular instant messaging client that supports a wide variety of IM protocols, including AIM, ICQ, MSN, Yahoo!, and Jabber. Although it was originally written for Linux, it now runs on most popular operating systems, including Windows and Mac OS X. Although exact user statistics are impossible to obtain, its users number in the hundreds of thousands, if not over a million. It’s so popular because, in addition to functionality available in other clients, it offers many unique features and is infinitely extensible through a powerful plug-in API. Most importantly in the context of this book is that Gaim is free and open source software.